ZIF-8 derived CeO₂-Fe₃O₄@Fe-N/C catalyst for oxygen reduction reaction - Hao, Yanqi (2022)
Looking for non-noble metal catalysts with low cost, high activity, and high stability to replace platinum in oxygen reduction reaction (ORR) has aroused great concern. According to previous studies, Fe-Nx/C material is one of the most promising non-noble metal catalysts for ORR. In this study, new Fe-Nx/C material was synthesized by introducing CeO2 and Fe3O4 nanoparticles into a Fe-Nx/C material derived from ZIF-8 as precursors. The new material was called CeO2-Fe3O4@Fe-N/C catalyst and the activity of the catalyst was found to be significantly improved in 0.1 mol L−1 KOH. The half-wave potential of CeO2-Fe3O4@Fe-N/C (0.892 V) is higher than that of Pt/C by 67 mV. In the stability test, the half-wave potential of CeO2-Fe3O4@Fe-N/C was only reduced by 4 mV after 5,000 cycles. The high performance is attributed to the introduction of CeO2 and Fe3O4, which gives CeO2-Fe3O4@Fe-N/C enhanced electrocatalytic activity and long-term stability. This approach makes CeO2-Fe3O4@Fe-N/C a promising candidate for cathode catalysts in renewable energy conversion devices.